A comprehensive survey on Bangla handwritten numeral recognition. (2018) - Singh, Pawan Kumar; Sarkar, Ram; Nasipuri, Mita
Handwritten numeral recognition is one of the traditional dilemma in pattern recognition domain, and is widely used in different applications such as reading postal codes, bank cheques etc. In this paper, we present a review work on handwritten digit recognition, focusing on Bangla script, the most popular script in India. We have summarised most of the published papers on this topic and have also analysed the various methodologies and their detailed consequences. Future directions of research in handwritten digit recognition on Bangla script have also been delivered which, in turn, will provide a better platform for further research activities.